The burden of common skin diseases assessed with the EQ5D™: a European multicentre study in 13 countries. (10th April 2017) - Balieva, F.; Kupfer, J.; Lien, L.; Gieler, U.; Finlay, A.Y.; Tomás‐Aragonés, L.; Poot, F.; Misery, L.; Sampogna, F.; van Middendorp, H.; Halvorsen, J.A.; Szepietowski, J.C.; et al.
Summary: Background: Generic instruments measuring health‐related quality of life (HRQoL), like EQ5D™, enable comparison of skin diseases with healthy populations and nondermatological medical conditions, as well as calculation of utility data. Objectives: To measure HRQoL in patients with common skin diseases and healthy controls across Europe using the EQ5D. Methods: This multicentre observational cross‐sectional study was conducted in 13 European countries. Each dermatology clinic recruited at least 250 consecutive adult outpatients to complete questionnaires, including the EQ5D. Results: There were 5369 participants (4010 patients and 1359 controls). Mean ± SD self‐rated health state reported by patients was 69·9 ± 19·7; for controls it was 82·2 ± 15·5. When adjusted for confounding factors, including comorbidity, mean patient EQ visual analogue scores were 10·5 points lower than for controls (standardized β = −0·23). Odds ratio with 95% confidence interval for impairment in all five dimensions of EQ5D adjusted for confounders was doubled for patients compared with controls. Patients with hidradenitis suppurativa (HS), blistering conditions, leg ulcers, psoriasis and eczemas had the highest risk for reduction in HRQoL in most dimensions (2–10‐fold). Data on differences of impairment by dimensions offer new insights. Conclusions: This study confirms the large impact skin conditions have on patients' well‐being, differentiating between aspects of HRQoL. Patients with HS, blistering diseases, leg ulcers, infections and most chronic skin diseases reported reduced HRQoL compared with patients with chronic obstructive lung disease, diabetes mellitus, cardiovascular disease and cancers. These findings are important in the prioritization of resource allocation between medical fields and within dermatological subspecialities. Abstract : What is already known about this topic? The EQ5D™ can be used to compare life quality impairment from diseases across a range of specialties and to generate utility data. The EQ5D has previously been little used in dermatology. What does this study add? This study has generated EQ5D data across a range of dermatological diagnoses in a large cohort of patients across Europe. Skin diseases affect quality of life differently across different dimensions. This EQ5D information may assist appropriate care and resource allocation. Respond to this article